Ninety-six–hour starved peripheral blood mononuclear cell supernatant inhibited LA7 breast cancer stem cells induced tumor via reduction in angiogenesis and alternations in Gch1 and Spr expressions - Mehri, Maryam; Gheitasi, Reza; Pourbagher, Roghayeh; Ranaee, Mohammad; Nayeri, Kosar; Rahimi, Seyed Mostafa; Khorasani, Hamid Reza; Hossein-Nattaj, Hadi; Sabour, Davood; Akhavan-Niaki, Haleh; Fattahi, Sadegh; Kalali, Behnam; et al. (Frontiers in Immunology, 2023)
Introduction The microenvironment of solid tumors such as breast cancer is heterogeneous and complex, containing different types of cell, namely, cancer stem cells and immune cells. We previously reported the immunoregulatory behavior of the human immune cell in a solid tumor microenvironment-like culture under serum starvation stress for 96 h. Here, we examined the effect of this culture-derived solution on breast cancer development in rats. Method Ninety-six–hour starved PBMCs supernatant (96 h-SPS) was collected after culturing human PBMCs for 96 h under serum starvation condition. Breast cancer stem cells, LA7 cell line, was used for in vitro study by analyzing gene expression status and performing cytotoxicity, proliferation, scratch wound healing assays, followed by in vivo tumor induction in three groups of mature female Sprague Dawley rats. Animals were treated with 96 h-SPS or RPMI and normal saline as control, n = 6 for each group. After biochemical analysis of iron, lactate, and pH levels in the dissected tumors, Ki67 antigen expression, angiogenesis, and necrosis evaluation were carried out. Metabolic-related gene expression was assessed using RT-qPCR. Moreover, 96 h-SPS composition was discovered by Nano-LC-ESI-MS/MS. Results 96 h-SPS solution reduced the LA7 cell viability, proliferation, and migration and Gch1 and Spr genes expression in vitro (p< 0.05), whereas stemness gene Oct4 was upregulated (p< 0.01). The intracellular lactate was significantly decreased in the 96 h-SPS treated group (p = 0.007). In this group, Gch1 and Spr were significantly downregulated (p< 0.05), whereas the Sox2 and Oct4 expression was not changed significantly. The number of vessels and mitosis (Ki67+ cells) in the 96 h-SPS–treated group was significantly reduced (p = 0.024). The increased rate of necrosis in this group was statistically significant (p = 0.04). Last, proteomics analysis revealed candidate effectors’ components of 96 h-SPS solution. Conclusion 96 h-SPS solution may help to prevent cancer stem cell mediated tumor development. This phenomenon could be mediated through direct cytotoxic effects, inhibition of cell proliferation and migration in association with reduction in Gch1 and Spr genes expression, angiogenesis and mitosis rate, and necrosis augmentation. The preliminary data obtained from the present study need to be investigated on a larger scale and can be used as a pilot for further studies on the biology of cancer development.